Experiential approaches to personal transformations: outward journeys and inward adventures - Hodgson, Brandy C., author; Kees, Nathalie, advisor; Kennedy, Cathy, advisor; Banning, James, committee member; Deniston, Terry, committee member (Colorado State University. Libraries, 2007)
This is the story of a group of seventeen late-adolescents who participated in a six week experiential immersion program through their alternative high school. The program, designed to serve as a rite of passage assisting these students in their transition toward adulthood, allowed them to participate in personal growth work, adventure travel, language and cultural immersion, and service to others. Four major units comprised the entire experiential education program. These included pre-trip retreat and requirements, four weeks of domestic "school within a school" immersion preparation, two weeks of international immersion in Chile, South America, and reintegration components upon return to the United States. Each of these four units was an immersion experience of its own and the curricular components were fairly consistent in that education was holistic, including physical, cognitive, social and emotional aspects of challenge and learning. Throughout the program students were asked to focus on personal growth and group dynamics, service to others, physical adventure activities, and intellectual development. This qualitative research study sought to describe the program, the students involved, and the outcomes attributed to participation in order to answer the question of how meaning was made through the experience. Changes in participants which were attributed to participation in the experiential program have been termed "inward", "outward", and "upward" to describe the intrapersonal and interpersonal changes, as well as the encompassing and holistic "Experiential Transformations" which occurred. The qualities which were deemed transformational changes included increased senses of self awareness and clarity, commitment to sobriety, developing self confidence, and an appreciation of growth through discomfort. Some students identified that the program had served for them as a transition from their teen years toward adulthood. These broad changes, termed experiential transformations, were defined through this study as holistic, beneficial and empowering personal and interpersonal changes, attributed to participation in an event or series of events. A model was developed to represent the interplay of cognitive, emotional, and experiential elements throughout the program which may have provided opportunities for these holistic changes and transformations to occur.
Keywords: secondary education; curricula; teaching; curriculum development